2014
DOI: 10.1093/ejcts/ezu439
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonectomy for benign disease: indications and postoperative outcomes, a nationwide study†

Abstract: Pneumonectomy for benign disease achieves cure with very high levels of morbidity and mortality. This type of surgical treatment should be considered as a salvage procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…One dog and two cats died or were euthanatized within the first 2 weeks postoperative. In people, pneumonectomy is also associated with high morbidity and a recent study of 5,975 people reported complications in 53% with benign disease and 39% with neoplastic disease . In that study, the postoperative in‐hospital mortality was 22% and 5% for people with benign and malignant disease, respectively .…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…One dog and two cats died or were euthanatized within the first 2 weeks postoperative. In people, pneumonectomy is also associated with high morbidity and a recent study of 5,975 people reported complications in 53% with benign disease and 39% with neoplastic disease . In that study, the postoperative in‐hospital mortality was 22% and 5% for people with benign and malignant disease, respectively .…”
Section: Discussionmentioning
confidence: 87%
“…Outcome after pneumonectomy in people is associated with a high morbidity and mortality . Recent studies reported a 30 day mortality of 5 and 5.7% in people undergoing pneumonectomy for cancer.…”
mentioning
confidence: 99%
See 3 more Smart Citations